Penerapan Metode Scramble dalam Pembelajaran Pendidikan Agama Kristen untuk Meningkatkan Hasil Belajar Siswa - Agnes Monica Halawa (UKI Press, 2021)
In the learning process the teacher needs a method as a means, a technique for conveying material and achieving the learning objectives itself. The scramble method is on of interesting learning methods to be applied in the learning process, especially for Christian religious education because it helps concentration and thinking speed of student in learning. The purpose of this study by applying the scramble method is the researcher wanted to improve learning outcomes of student in Christian religious education at Tunas Cemerlang primary school, East Jakarta with a total of 10 christian students consisting of 4 female students and 6 male students. The method used in this research is classroom action research (PTK) carried out in two cycles in one learning year or one cycle in one semester. In each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The application of the scramble method to improve student learning outcomes in Christian religious education resulted in cycle I (50%) students were able to successfully achieve learning outcomes in according with the minimum completenees criteria and cycle II showed an increase with the results of (80%) students successfully achieving learning outcomes above the minimum completeness criteria in chirstian religious education subjects. The application of the scramble method can done in Christian religious education learning to achieve the objectives of this study in improving learning outcomes, but also helping to increase activity of teacher and student activity. The scramble method also helps the learning process of Christian religious education to be not boring.